Vertov et la perception-caméra (Cinéma & Cie. Film and Media Studies Journal, 2019)
This article approaches cinema through a transdisciplinary perspective joining philosophy with moving-image practice to think time, subjectivity, objectivity – and relationality. Working from the example of Dziga Vertov’s Man With a Movie Camera film, it explores the idea of the perception-camera as a relational point of view through which the film, as an event, evolves. It understands the film as an autonomous entity evolving through this relational point of view. In so doing, it fosters a complex approach beyond the subjective-objective perspective, and discusses what Gilles Deleuze calls the “free indirect image.” This is the point of view of an unfolding subjective form that does not pertain to human perspective, but to the event perceiving itself as it evolves into its own accomplishment.